Evaluation of Teaching Campus With Context, Input, Process, and Product (CIPP) Model In Primary School - Ervina Damayanti; Avinta Ika Nurrahma; Emilia Ainur Rohmah (Program Studi Pendidikan Guru Madrasah Ibtidaiyah INSURI Ponorogo, 2024)
Alfie Ridho, Arina Denggan Munthe, Dimas Andika Shaputra, Indah Wahyuni, Lutfhia Farhana Putri Lubis, Nursiti Maysarah, & Inom Nasution. (2023). Analysis of Education Programme Evaluation in School Learning. Journal of Education, Language and Culture, 2(2), 211-221. https://doi.org/10.55606/jpbb.v2i2.1516 Anugrah, T. M. F. (2021). Implementation of the Teaching Campus Programme Batch 1 Affected by the Covid-19 Pandemic. AKSELERASI: National Scientific Journal, 3(3), 38-47. https://doi.org/10.54783/jin.v3i3.458 Bhakti, Y. B. (2022). Learning Evaluation in education. Bintang Madani. Daryono, D. (2023). The Foundation of Education in Merdeka Learning Independent Campus. Adanu Abimata. Divayana, D. G. H. (2018). Programme Evaluation Basic Concepts and Implementation. RajaGrafindo Persada. Efendi, R., Lubis, J., & Elvina, E. (2020). The Effect of Wages and Employee Incentives on Employee Performance at Pt. Milano Panai Tengah. Ecobisma (Journal of Economics, Business and Management), 7(2), 1-11. https://doi.org/10.36987/ecobi.v7i2.1759 Efendi, S. F., & Rozie, F. (2024). Actualisation of the Teaching Campus Program through the Implementation of Rich Literacy and Numeracy Activities at SD Negeri Dungkek III. Satya Widya, 40(1), 100-111. https://doi.org/10.24246/j.sw.2024.v40.i1.p100-111 Femica, N. A. (2024). The Effectiveness of the Merdeka Learning Campus Merdeka (MBKM) Programme in Improving the Work Readiness of Students of the Untirta Non-Formal Education Department. Sultan Ageng Tirtayasa. Fridiyanto, D. (2022). Merdeka Belajar Kampus Merdeka. Eternal Nusantara Literacy. Hajaroh, M. (2019). THEORY POHON OF POLICY AND PROGRAMME EVALUATION (Methods, Values and Assessments, Uses). Foundasia, 9(1), 27-42. https://doi.org/10.21831/foundasia.v9i1.26149 Haniyuhana, A., & Katerina Bataha. (2022). Policy Evaluation of Campus Teaching Programme Batch 3 at Tumbrep 01 State Elementary School. Journal of Basic Education, 13(2), 53-66. https://doi.org/10.21009/jpd.v13i2.28385 Ibrahim, mysikat M. (2018). Evaluation Research in Education (Evaluative Approach). Alauddin University Press. Kurniati, Agusta, D. (2024). IMPLEMENTATION OF LITERACY AND NUMERACY IN IMPLEMENTATION Introduction The implementation of educational policy changes that are currently being discussed, one of which is the change in policy on this curriculum in the end makes a learning process. 10 (April), 154-166. Kusumawardani, S. S., Wulandari, D., Arifin, S., Santoso, B. J., Cahyono, E., Wastutiningsih, S. P., Slamet, A. S., Hertono, G. F., Yuniarti, A., Syam, N. M., Putra, P. H., Rahmawati, A., Fajri, F., Zuliansyah, A., Yulianto, Y., Julyan, B. S., Anggriani, D., & Nabila, S. Z. (2024). Guidebook for Merdeka Campus Learning. Directorate General of Higher Education, Research, and Technology, 98. https://dikti.kemdikbud.go.id/wp-content/uploads/2024/06/Buku-Panduan-Merdeka-Belajar-Kampus-Merdeka-MBKM-2024.pdf Lengkong, J. (2023). Supervision & Evaluation of Education. Litnus. Mahmudi, I. (2011). CIPP: A Model of Educational Programme Evaluation. At-Ta'dib, 6(1). https://doi.org/10.21111/at-tadib.v6i1.551 Nashirulhaq, N., Nurzaelani, M. M., & Raini, Y. (2022). The Importance of Basic Literacy and Numeracy Skills in Junior High School Education. Proceedings, 118-122. http://pkm.uika-bogor.ac.id/index.php/PTP/article/download/1313/974 Nurafifah. (2023). Implementation of Technology Adaptation of Campus Students Teaching at SDN 141 Cennae, Soppeng Regency. Journal of Educational Technology, Curriculum, Learning, and Communication, 3, 1-6. Nurcahyono, N. A. (2023). Improving Numeracy Literacy Skills through Learning Models. Hexagon: Journal of Mathematics Science and Education, 1(1), 20. https://doi.org/10.33830/hexagon.v1i1.4924 Nurjanah, B., Hamidah, D., & ... (2024). The Role of Campus Students Teaching-6 Regarding the Introduction and Understanding of Technology Adaptation Regarding Literacy Issues and .... Journal Serunai ..., 13(1). https://www.ejournal.stkipbudidaya.ac.id/index.php/jc/article/view/1216%0Ahttps://www.ejournal.stkipbudidaya.ac.id/index.php/jc/article/download/1216/713 Rahman, A. A. C. E. (2019). Learning Evaluation. Uwais Inspirasi Indonesia. Rusandi, & Muhammad Rusli. (2021). Designing Basic/Descriptive Qualitative Research and Case Studies. Al-Ubudiyah: Journal of Education and Islamic Studies, 2(1), 48-60. https://doi.org/10.55623/au.v2i1.18 Thanzani, A. (2022). The Role of Students in the Teaching Campus Programme in 3T (Disadvantaged, Outermost, and Frontier) Areas. PSHPM: Proceedings of the Activity Results Seminar, 213-222. https://conference.untag-sby.ac.id/index.php/scfp/article/view/742 Tulung, J. M. (2014). Evaluation of Level IV Leadership Education and Training Programme at Manado Religious Education and Training Centre. Journal